Determinants of post-partum amenorrhea among Nepalese rural mothers: A multivariate analysis - Aryal, TR (Kathmandu University Medical Journal, 2010)
Introduction: Post-partum amenorrhea (PPA) is the duration variable, which is directly related to the levels of fertility. The timing of occurrence of the first menstruation after delivery is known as the duration of PPA. It is a temporary infecundable period where mothers are most likely to be free from possible conception. Objective: This paper investigates the determinants of the duration of PPA in relation to some characteristics of mother and her child by using both current as well as retrospective status reporting data. Materials and methods: Data are taken from a sample survey of rural Palpa and Rupandehi districts. A sample of 1019 ever-married mothers was interviewed. Of them, 642 mothers were provided PPA information for their last birth child, and 481 mothers were provided PPA information for their last but one child. Cox proportional hazard model analysis has been utilized to identify the determinants of PPA duration. Results: A lower relative risk of PPA period was found among mothers who have higher parity, larger birth interval and longer period of breastfeeding (BF). Education was inversely associated with PPA, and about 1.5 times higher risk of returning menstruation early was found among educated mothers as compared uneducated counter-part. BF is significantly associated with PPA where the longer is the duration of BF the longer is the duration of PPA. The relative risk was found increased with increases the level of socio-economic status. Over twice times higher risk of returning menstruation early was found among mothers who had experienced dead child as compared to mothers who have no child loss. Conclusion: The variables like birth interval, parity, breastfeeding, education, socio-economic status and child survival are found the main determinants of PPA duration among Nepalese mothers. Key words: Post-partum amenorrhea; breastfeeding; fertility DOI: 10.3126/kumj.v8i1.3214 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 5-11